2020
DOI: 10.3390/jcm10010121
|View full text |Cite
|
Sign up to set email alerts
|

Side Effect/Complication Risk Related to Injection Branch Level of Chemoembolization in Treatment of Metastatic Liver Lesions from Colorectal Cancer

Abstract: Purpose: Transarterial chemoembolization with drug eluting beads (DEB-TACE) loaded with irinotecan despite having proven efficacy in the treatment of unresectable liver metastases in the course of colorectal cancer (CRC) does not have an established consistent method. In particular, there are discrepancies in the branch level at which microspheres are administered. Lobar embolization supplies microspheres to all vessels supplying a metastatic lesion but exposes the entire liver parenchyma to negative effects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To avoid the occurrence of serious complications, selective catheterization and slow infusion of the embolic material were performed in the present case. In addition, the results of a previous study demonstrated that post-embolization syndrome is closely associated with the side effects of chemotherapy drugs ( 49 ). Thus, self-made gelatin sponges were used in the present study to replace the chemotherapy drugs and result in fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the occurrence of serious complications, selective catheterization and slow infusion of the embolic material were performed in the present case. In addition, the results of a previous study demonstrated that post-embolization syndrome is closely associated with the side effects of chemotherapy drugs ( 49 ). Thus, self-made gelatin sponges were used in the present study to replace the chemotherapy drugs and result in fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Irinotecan-TACE is generally well tolerated with serious adverse events (AEs) experienced in about 0–10% of patients [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, grade 1 and 2 post-embolization syndrome (PES) after a treatment session is a common occurrence (10–60%) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Although there are recommendations regarding treatment plans [ 25 , 26 ], such as to perform at least two sessions for unilobar and four sessions for bilobar disease and regarding technical considerations like the use of opioids, intra-arterial anesthetic, and antiemetics, recent literature has highlighted the lack of standardized technical protocols [ 11 ].…”
Section: Introductionmentioning
confidence: 99%